Hubungan Pembelajaran Pendidikan Kewarganegaraan Dengan Pembentukan Karakter Peserta Didik - ., Uswatun Hasanah; ., Alfiatus Syarofah; ., Halimah; ., Indani Khoirun Nisak (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
This study aims to determine the relationship between learning civics education and the formation of students' character, knowing what character education is, and the role of teachers in civics education in the formation of students' character. Citizenship education is an integral part of the national education system. Character education is good or superior, a system of instilling character values ​​in school members which includes components of knowledge, awareness or will, and actions to implement these values. This research uses descriptive method and qualitative approach. The results of this study indicate that the learning of citizenship education in schools has a relationship with the formation of the character of students, and also the teacher has an important role in the formation of good character for students because what the teacher does will certainly be emulated by students because they consider what is done by the teacher is true especially as a civics education teacher.